Synthesis and acetylcholinesterase inhibitory activity of polyhydroxylated sulfated steroids: structure/activity studies - Richmond, Victoria (2013)
Disulfated and trisulfated steroids have been synthesized from cholesterol and their acetylcholinesterase inhibitory activity has been evaluated. In our studies we have found that the activity was not only dependent on the location of the sulfate groups but on their configurations. 2β,3α,6β-trihydroxy-5α-cholestan-6-one trisulfate (18) was the most active steroid with an IC50 value of 15.48 μM comparable to that of 2β,3α-dihydroxy-5α-cholestan-6-one disulfate (1). Both compounds were found to be less active than the reference compound eserine. The butyrylcholinesterase activity of 1 and 18 was one magnitude lower than that against acetylcholinesterase revealing a selective inhibitor profile.